Frequency of self-monitoring of blood glucose in relation to weight loss and A1C during intensive multidisciplinary weight management in patients with type 2 diabetes and obesity - Tomah, Shaheen (BMJ Open Diabetes Res Care, 2019)
OBJECTIVE: We evaluated the relationship between frequency of self-monitoring of blood glucose (SMBG) and body weight, A1C, and cardiovascular risk factors in patients with type 2 diabetes (T2D) and obesity enrolled in a 12-week intensive multidisciplinary weight management (IMWM) program. RESEARCH DESIGN AND METHODS: We conducted a retrospective analysis of 42 patients who electronically uploaded their SMBG data over 12 weeks of an IMWM program and divided them into tertiles based on their average frequency of SMBG per day. Mean (range) SMBG frequencies were 2.3 (1.1–2.9) times/day, 3.4 (3–3.9) times/day, and 5 (4–7.7) times/day in the lowest, middle, and highest tertiles, respectively. Anthropometric and metabolic parameters were measured at baseline and after 12 weeks of intervention. RESULTS: Participants in the highest tertile achieved a median change (IQR) in body weight of −10.4 kg (−7.6 to −14.4 kg) compared with −8.3 kg (−5.2 to −12.2 kg), and −6.9 kg (−4.2 to −8.9 kg) in the middle and lowest tertiles, respectively (p=0.018 for trend). Participants in the highest tertile had a median change (IQR) in A1C of −1.25% (−0.6 to −3.1%) compared with −0.8% (−0.3% to −2%) and −0.5% (−0.2% to −1.2%) in the middle and lowest tertiles, respectively (p=0.048 for trend). The association between change in body weight and SMBG frequency remained significant after adjusting for age, sex, baseline body mass index, diabetes duration, and use of insulin therapy. CONCLUSIONS: Increased frequency of SMBG during IMWM is associated with significantly better weight loss and improvement of A1C in patients with T2D and obesity. These findings may suggest future clinical recommendations aimed at increasing SMBG frequency to achieve the most favorable outcomes.